Analysis of Al2O3 layers morphology and microstructure - Skoneczny, W. (Фізико-хімічна механіка матеріалів, 2010)
The paper presents the characterization of obtaining Al2O3 oxide layers on aluminium AlMg2 alloy as a result of hard anodizing by the electrolytic method in a three-component electrolyte. The Al2O3 layers obtained on the AlMg2 alloy in the three-component SBS electrolyte were subjected to detailed microstructural investigations (by means of a scanning electron microscope, SEM). By applying X-ray diffraction, examination of the obtained oxide layers phase compositions was carried out. It was found that the Al2O3 oxide layers obtained via hard anodizing in a three-component electrolyte are amorphous. The chemical composition of the Al2O3 layers is presented and compared to the results of stechiometric calculations for the Al2O3 layer. Surface morphologies of the obtained oxide layers are characterized and discussed in nano- and microscopic scales. The surface morphologies of the layers obtained have a significant influence on their properties, including their susceptibility to further modification (e.g. to incorporation of graphite), their wear resistance and the capacity for sorption of lubricants.